Arrangement of The Marine Biodive Natural Resources Conservation in The Coastal of Sendana District, Majene Regency - Laitupa, Salma (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
Arrangements for the conservation of living natural resources in the sea, are explicitly regulated in UNCLOS 1982 concerning the protection and preservation of the marine environment which places obligations on participating countries to protect and maintain the marine environment. The provisions of Article 192 UNCLOS 1982 stipulate that every State has an obligation to protect and preserve the marine environment. Therefore, the state has the responsibility to ensure that activities within its jurisdiction or control do not cause damage to the environment of other countries or areas outside the boundaries of national jurisdiction. This means that the marine environment is an important part and must be maintained and preserved by every country.